The Phenotype and Treatment of WIP Deficiency: Literature Synopsis and Review of a Patient With Pre-transplant Serial Donor Lymphocyte Infusions to Eliminate CMV - Schwinger, Wolfgang; Urban, Christian; Ulreich, Raphael; Sperl, Daniela; Karastaneva, Anna; Strenger, Volker; Lackner, Herwig; Boztug, Kaan; Albert, Michael H.; Benesch, Martin; Seidel, Markus G. (Frontiers in Immunology, 2018)
Early diagnosis of primary immunodeficiency disorders (PID) is vital and allows directed treatment, especially in syndromes with severe or profound combined immunodeficiency. In PID patients with perinatal CMV or other opportunistic, invasive infections (e.g., Pneumocystis or Aspergillus), multi-organ morbidity may already arise within the first months of life, before hematopoietic stem cell transplantation (HSCT) or gene therapy can be undertaken, compromising the definitive treatment and outcome. Deficiency of Wiskott-Aldrich syndrome (WAS) protein-interacting protein (WIP deficiency) causes an autosomal recessive, WAS-like syndrome with early-onset combined immunodeficiency that has been described in three pedigrees to date. While WAS typically includes combined immunodeficiency, microthrombocytopenia, and eczema, the clinical and laboratory phenotypes of WIP-deficient patients—including lymphocyte subsets, platelets, lymphocyte proliferation in vitro, and IgE—varied widely and did not entirely recapitulate WAS, impeding early diagnosis in the reported patients. To elucidate the phenotype of WIP deficiency, we provide a comprehensive synopsis of clinical and laboratory features of all hitherto-described patients (n=6) and WIP negative mice. Furthermore, we summarize the treatment modalities and outcomes of these patients and review in detail the course of one of them who was successfully treated with serial, unconditioned, maternal, HLA-identical donor lymphocyte infusions (DLI) against life-threatening, invasive CMV infection, followed by a TCRαβ/CD19-depleted, treosulfan/melphalan-conditioned, peripheral blood HSCT and repetitive, secondary-prophylactic, CMV-specific DLI with one-year post-HSCT follow-up. This strategy could be useful in other patients with substantial premorbidity, considered “too bad to transplant”, who have an HLA-identical family donor, to eliminate infections and bridge until definitive treatment.